The Alpine Tethys rifted margins: Reconciling old and new ideas to understand the stratigraphic architecture of magma‐poor rifted margins. Issue 1 (23rd January 2013) - Masini, Emmanuel; Manatschal, Gianreto; Mohn, Geoffroy; Weissert, Helmut
Abstract This study focuses on the assessment of the stratigraphic architecture of the proximal and distal Jurassic Alpine Tethys rifted margins. The aim of the study was to reconcile the major observations performed in the Alps through time with what is observed in present‐day magma‐poor rifted margins. The proximal and distal rifted margins reflect two evolutionary phases of rifting involving different structures and isostatic evolutions leading to different stratigraphic records. The proximal rifted margins formed from Upper Triassic to Pliensbachian times and resulted in the formation of classical half graben basins. Rift evolution changed drastically during Pliensbachian to Toarcian times when extension started to localize in the future distal rifted margins. Low‐angle detachment faults become the new elementary structure controlling final crustal tapering and eventually mantle exhumation to the sea floor. New structural elements controlling the stratigraphic architecture of the distal rifted margins include extensional allochthons and breakaway blocks, both resulting from the delamination of a keystone block, also referred to as hangingwall block, during hyper‐extension processes. To define the stratigraphic architecture of the proximal and distal rifted margins, three stratigraphic marker horizons are used, namely the top of the pre‐rift sequences, the top of the proximal margin syn‐tectonic sequence and the base of post‐rift sequences. Based on the distribution of these stratigraphic marker horizons across the Alpine units and a structural re‐evaluation of the rift structures, a synthetic tectono‐stratigraphic evolution of the Alpine Tethys domain is proposed that reconciles old and new ideas about how rift systems may evolve in space and time.